Against Unchecked Price Intervention: Maslahah ‘Ammah and Ta’sir in Islamic Economic Law - Sofi Faiqotul Hikmah (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2026)
Market distortion in the form of hoarding, monopoly, fraud, cartel behavior, and manipulation of supply shows that price formation does not always reflect fairness. In Islamic economic law, state intervention in market prices, known as tasʿīr, remains a debated issue because the Prophet refused to impose prices in a market that operated naturally. However, contemporary market conditions often require public authority to prevent exploitation and protect access to essential goods. This article analyzes maṣlaḥah ‘āmmah as a legal-ethical criterion for assessing the legitimacy of tasʿīr for consumers, producers, and the state. Normative-conceptual legal research is employed through library research on Qurʾānic verses, Hadith reports, tafsīr works, uṣūl al-fiqh literature, maqāṣid al-sharīʿah, and public policy studies. The analysis uses thematic tafsīr, maqāṣid reasoning, and public policy analysis. The findings show that tasʿīr is legitimate when market prices are distorted by harmful practices and when intervention protects public welfare without creating new injustice. Mashlaḥah ‘āmmah in tasʿīr must therefore be understood as proportional protection of consumers, producers, and the state through a policy framework grounded in naṣṣ, maqāṣid al-sharīʿah, evidence, and accountability.  Penetapan harga oleh negara dalam konsep tasʿīr tidak dapat dilepaskan dari persoalan keadilan pasar. Harga yang terbentuk melalui mekanisme permintaan dan penawaran dapat diterima selama pasar berjalan wajar. Persoalan muncul ketika harga dipengaruhi oleh penimbunan, monopoli, kartel, kecurangan, manipulasi pasokan, atau penguasaan distribusi oleh aktor tertentu. Artikel ini menganalisis maṣlaḥah ‘āmmah sebagai ukuran legal-etis dalam menilai legitimasi tasʿīr bagi konsumen, produsen, dan negara. Penelitian ini menggunakan metode hukum normatif-konseptual melalui studi kepustakaan terhadap ayat-ayat al-Qurʾān, Hadis, tafsir, literatur uṣūl al-fiqh, maqāṣid al-sharīʿah, dan kajian kebijakan publik. Analisis dilakukan dengan pendekatan tafsir tematik, penalaran maqāṣid, dan analisis kebijakan publik. Hasil penelitian menunjukkan bahwa tasʿīr dapat dibenarkan apabila harga pasar tidak lagi mencerminkan kewajaran, tetapi terbentuk melalui praktik yang menimbulkan mafsadah. Legitimasi tasʿīr tidak cukup didasarkan pada klaim kepentingan publik, tetapi harus diuji melalui perlindungan yang proporsional terhadap konsumen, produsen, dan negara. Mashlaḥah ‘āmmah dalam tasʿīr menuntut kebijakan harga yang berbasis naṣṣ, maqāṣid al-sharīʿah, bukti kerusakan pasar, proporsionalitas, transparansi, dan akuntabilitas.